Helicobacter pylori outer inflammatory protein A (OipA) suppresses apoptosis of AGS gastric cells in vitro. (25th August 2017) - Al‐Maleki, Anis Rageh; Loke, Mun Fai; Lui, Sook Yin; Ramli, Nur Siti Khadijah; Khosravi, Yalda; Ng, Chow Goon; Venkatraman, Gopinath; Goh, Khean‐Lee; Ho, Bow; Vadivelu, Jamuna
Abstract: Outer inflammatory protein A (OipA) is an important virulence factor associated with gastric cancer and ulcer development; however, the results have not been well established and turned out to be controversial. This study aims to elucidate the role of OipA in Helicobacter pylori infection using clinical strains harbouring oipA "on" and "off" motifs. Proteomics analysis was performed on AGS cell pre‐infection and postinfection with H . pylori oipA "on" and "off" strains, using liquid chromatography/mass spectrometry. AGS apoptosis and cell cycle assays were performed. Moreover, expression of vacuolating cytotoxin A (VacA) was screened using Western blotting. AGS proteins that have been suggested previously to play a role or associated with gastric disease were down‐regulated postinfection with oipA "off" strains comparing to oipA "on" strains. Furthermore, oipA "off" and Δ oipA cause higher level of AGS cells apoptosis and G0/G1 cell‐cycle arrest than oipA "on" strains. Interestingly, deletion of oipA increased bacterial VacA production. The capability of H . pylori to induce apoptosis and suppress expression of proteins having roles in human disease in the absence of oipA suggests that strains not expressing OipA may be less virulent or may even be protective against carcinogenesis compared those expressing OipA. This potentially explains the higher incidence of gastric cancer in East Asia where oipA "on" strains predominates.